HUBUNGAN TINGKAT PENDIDIKAN PERAWAT INSTALASI GAWAT DARURAT DENGAN KEPATUHAN PELAKSANAAN STANDAR PROSEDUR OPERASIONAL PENERIMAAN PASIEN BARU DI RSUD AM PARIKESIT TENGGARONG - Alfi Ari Fahkrur (Universitas Muhammadiyah Kalimantan Timur, 2017)
quick and precise service is urgently needed in the service of the IGD. However, the service at IGD can be hampered if the condition in the IGD filled with patients. Such a condition can cause nurses overlook the importance of the implementation of Standards operating procedures. The purpose of the research: the relationship between the level of education of nurse Emergency Installation compliance with the implementation of Standards operating procedures the acceptance of new patients. Research methods: use a descriptive analytic design research with cross sectional approach. Sample totaled 32 respondents obtained using total Sampling. The collection of data using a detailed questionnaire and observation sheets were analyzed using Fisher test Excat. Results: the results of the test statistics